A prospective evaluation of inter-rater agreement of routine medical records audits at a large general hospital in São Paulo, Brazil - Ana Carolina Cintra Nunes Mafra; João Luiz Miraglia; Fernando Antonio Basile Colugnati; Gilberto Soares Lourenço Padilha; Renata Rafaella Santos Tadeucci; Ederson Almeida; Mario Maia Bracco (BMC, 2020)
Abstract Background The quality of patient medical records is intrinsically related to patient safety, clinical decision-making, communication between health providers, and continuity of care. Additionally, its data are widely used in observational studies. However, the reliability of the information extracted from the records is a matter of concern in audit processes to ensure inter-rater agreement (IRA). Thus, the objective of this study is to evaluate the IRA among members of the Patient Health Record Review Board (PHRRB) in routine auditing of medical records, and the impact of periodic discussions of results with raters. Methods A prospective longitudinal study was conducted between July of 2015 and April of 2016 at Hospital Municipal Dr. Moysés Deutsch, a large public hospital in São Paulo. The PHRRB was composed of 12 physicians, 9 nurses, and 3 physiotherapists who audited medical records monthly, with the number of raters changing throughout the study. PHRRB meetings were held to reach a consensus on rating criteria that the members use in the auditing process. A review chart was created for raters to verify the registry of the patient's secondary diagnosis, chief complaint, history of presenting complaint, past medical history, medication history, physical exam, and diagnostic testing. The IRA was obtained every three months. The Gwet's AC1 coefficient and Proportion of Agreement (PA) were calculated to evaluate the IRA for each item over time. Results The study included 1884 items from 239 records with an overall full agreement among raters of 71.2%. A significant IRA increase of 16.5% (OR = 1.17; 95% CI = 1.03-1.32; p = 0.014) was found in the routine PHRRB auditing, with no significant differences between the PA and the Gwet's AC1, which showed a similar evolution over time. The PA decreased by 27.1% when at least one of the raters was absent from the review meeting (OR = 0.73; 95% CI = 0.53-1.00; p = 0.048). Conclusions Medical record quality has been associated with the quality of care and could be optimized and improved by targeted interventions. The PA and the Gwet's AC1 are suitable agreement coefficients that are feasible to be incorporated in the routine PHRRB evaluation process.